Comparative analysis of throughfall observations in six different forest stands: Influence of seasons, rainfall‐ and stand characteristics - Blume, Theresa; Schneider, Lisa; Güntner, Andreas (Hydrological processes, 2022)
Throughfall, that is, the fraction of rainfall that passes through the forest canopy, is strongly influenced by rainfall and forest stand characteristics which are in turn both subject to seasonal dynamics. Disentangling the complex interplay of these controls is challenging, and only possible with long‐term monitoring and a large number of throughfall events measured in parallel at different forest stands. We therefore based our analysis on 346 rainfall events across six different forest stands at the long‐term terrestrial environmental observatory TERENO Northeast Germany. These forest stands included pure stands of beech, pine and young pine, and mixed stands of oak‐beech, pine‐beech and pine‐oak‐beech. Throughfall was overall relatively low, with 54–68% of incident rainfall in summer. Based on the large number of events it was possible to not only investigate mean or cumulative throughfall but also its statistical distribution. The distributions of throughfall fractions show distinct differences between the three types of forest stands (deciduous, mixed and pine). The distributions of the deciduous stands have a pronounced peak at low throughfall fractions and a secondary peak at high fractions in summer, as well as a pronounced peak at higher throughfall fractions in winter. Interestingly, the mixed stands behave like deciduous stands in summer and like pine stands in winter: their summer distributions are similar to the deciduous stands but the winter peak at high throughfall fractions is much less pronounced. The seasonal comparison further revealed that the wooden components and the leaves behaved differently in their throughfall response to incident rainfall, especially at higher rainfall intensities. These results are of interest for estimating forest water budgets and in the context of hydrological and land surface modelling where poor simulation of throughfall would adversely impact estimates of evaporative recycling and water availability for vegetation and runoff. Summer and winter distributions of throughfall fractions for six forest stands (transparent colouring to allow for full visibility of the overlapping distributions). Mixed stands (PB: Pine/Beech, PBO: Pine/Beech/Oak) have the summer peak at low fractions similar to the deciduous stands (B: Beech, OB: Oak/Beech) but their winter distributions resemble those of the pine stands (P: Pine, YP: young Pine), that is, they do not have the pronounced peak at high fractions as in the deciduous stands.